Higher prevalence and abundance of Bdellovibrio bacteriovorus in the human gut of healthy subjects. - Valerio Iebba (Public Library of Science (PLoS), 2013)
Introduction Members of the human intestinal microbiota are key players in maintaining human health. Alterations in the composition of gut microbial community (dysbiosis) have been linked with important human diseases. Understanding the underlying processes that control community structure, including the bacterial interactions within the microbiota itself, is essential. Bdellovibrio bacteriovorus is a gram-negative bacterium that preys other gram-negative species for survival, acting as a population-balancer. It was found in terrestrial/aquatic ecosystems, and in animal intestines, postulating its presence also in the human gut. Methods The present study was aimed to evaluate, by end-point PCR and qPCR, the presence of B. bacteriovorus in intestinal and faecal biopsy specimens from 92 paediatric healthy subjects and patients, suffering from Inflammatory Bowel Diseases (IBD), Celiac disease and Cystic fibrosis (CF). Results i) B. bacteriovorus was present and abundant only in healthy individuals, while it was heavily reduced in patients, as in the case of IBD and Celiac, while in CF patients and relative controls we observed comparable results; ii) B. bacteriovorus seemed to be mucosa-associated, because all IBD and Celiac biopsies (and related controls) were treated with mucus-removing agents, leaving only the mucosa-attached microflora; iii) B. bacteriovorus abundance was district-dependent, with a major preponderance in duodenum, and gradually decreasing up to rectum; iv) B. bacteriovorus levels significantly dropped in disease status, in duodenum and ileum. Conclusions Results obtained in this study could represent the first step for new therapeutic strategies aimed to restore a balance in the intestinal ecosystem, utilizing Bdellovibrio as a probiotic.